Effect of Bedding Structure on the Energy Dissipation Characteristics of Dynamic Tensile Fracture for Water-Saturated Coal - Shuang Gong; Lei Zhou; Zhen Wang; Wen Wang (Geofluids)
The analysis of energy dissipation characteristics is a basic way to elucidate the mechanism of coal rock fragmentation. In order to study the energy dissipation patterns during dynamic tensile deformation damage of coal samples, the Brazilian disc (BD) splitting test under impact conditions was conducted on burst-prone coal samples using a split Hopkinson pressure bar (SHPB) loading system. The effects of impact velocity, bedding angle, and water saturated on the total absorbed energy density, total dissipated energy density, and damage variables of coal samples were investigated. In addition, the coal samples were collected after crushing to produce debris with particle sizes of 0-0.2 mm and 0.2-5 mm, and the distribution characteristics of different size debris were compared and analyzed. The results show that the damage variables of natural dry coal samples increase approximately linearly with the increase of impact velocity; however, the overall damage variables of saturated coal samples increase exponentially as a function of impact velocity. Compared with air-dry samples, the number of fragments with the particle size of 0-0.2 mm of saturated samples decreases by 14.1%-31.3%, and the number of fragments with the particle size of 0.2-5 mm decreases by 33.7%-53.0%. However, when the bedding angle is 45°, the percentage of fragment mass of saturated samples is larger than that of air-dry samples. The conclusions provide a theoretical basis for understanding the deterioration mechanism of coal after water saturation and the implementation of water injection dust prevention technology in coal mines.